The role of international tourism in the development of the economy of Armenia - Grigorian D. O. (Scientific studies and modern education, 2019)
travel and tourism is an important key for accelerating and expanding economic development, investment and employment in Armenia with visitor numbers increasing year-on-year, growing private and public investment, and broad consumer satisfaction. Furthermore, according to Armenia’s National Development Strategy 2014–2025, tourism is one of five priority sectors for job creation. The strategy indicates that incoming tourism should retain its role as the second main export sector and will account for around 20 percent of exports.
Keywords: экономика; туризм; туристы; Tourism; economy; Армения; Armenia; путешествия; travel; tourists